Maoists' insurgency in India and Nepal: philosophy, logistic collaboration, ideological ties - Sinha, K.N. (Delhi, 2011)
The Maoists' insurgency which began in Nepal in the 1990's was mainly oriented to abolish the monarchy seen as an obstacle to the economic, social and political development of Nepal and another was the cancelling the "unequal" treaties with India in order to end the virtual control of the Nepalese economy by Indian business men. The present book touches varied aspects of Maoists comprising Maoists Conflict in the context of India and Nepal, Philosophy of Maoism, rise of Naxalism and Maoism in India, revolution in India, Indian Maoists and impact of global economic crisis etc.
Keywords: Maoist insurgency-India-Nepal